Library Book Return Compliance Model: A Case Study of Students at Universitas Negeri Padang - Muhammad Galang Pratama; Rini Asmara (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Timely book return is essential for maintaining collection availability and effective circulation services in university libraries. Nevertheless, late returns have been observed among Universitas Negeri Padang (UNP) students, while the behavioral factors underlying book-return compliance have received limited integrated attention. This study described UNP students’ book-return compliance using the Theory of Planned Behavior (TPB) as an analytical framework. A quantitative descriptive approach was employed involving 100 students. Data were collected using a 25-item questionnaire with a four-point Likert scale and analyzed through descriptive statistics. The findings yielded an overall mean compliance score of 87.33. Among the TPB dimensions, attitude obtained the highest score (91.10%), followed by behavioral intention (89.25%), perceived behavioral control (86.10%), behavior (85.65%), and subjective norm (84.55%). The 3.60-percentage-point difference between intention and behavior indicates an intention–behavior gap, suggesting that favorable intentions were not fully translated into compliant book-return behavior. The comparatively lower subjective-norm score further indicates that individual attitudes, intentions, and perceived control were more prominent than social influence. The study concludes that TPB provides a useful framework for profiling students’ book-return compliance and identifying the behavioral dimensions requiring institutional intervention. University libraries should strengthen communication, reminders, and return facilities to help translate students’ intentions into consistent compliance.